The Peripheral Blood Eosinophil Proteome - Wilkerson, Emily M. (J Proteome Res, 2016)
A system-wide understanding of biological processes requires a comprehensive knowledge of the proteins in the biological system. The eosinophil is a type of granulocytic leukocyte specified early in hematopoietic differentiation that participates in barrier defense, innate immunity, and allergic disease. The proteome of the eosinophil is largely unannotated with under 500 proteins identified. We now report a map of the nonstimulated peripheral blood eosinophil proteome assembled using two-dimensional liquid chromatography coupled with high-resolution mass spectrometry. Our analysis yielded 100,892 unique peptides mapping to 7,086 protein groups representing 6,813 genes as well as 4,802 site-specific phosphorylation events. We account for the contribution of platelets that routinely contaminate purified eosinophils and report the variability in the eosinophil proteome among five individuals and proteomic changes accompanying acute activation of eosinophils by interleukin-5. Our deep coverage and quantitative analyses fill an important gap in the existing maps of the human proteome and will enable the strategic use of proteomics to study eosinophils in human diseases.